Perbandingan Pemikiran, Perjuangan Dan Sumbangan Mahatma Gandhi Dan Tun V.t. Sambanthan - Chandran, Gangathran (2021)
This writing discusses the comparison of thoughts, struggles and contributions of Mahatma Gandhi and Tun V.T. Sambanthan. They were both nationalists and politicians from India and Malaya. The objective of this research is to explain the thoughts and struggles of Gandhi and Sambanthan while fighting for the rights of the society and the independence of their respective countries. Moreover, this research also analyzed the similarities and differences in their thoughts and struggles. Besides that, it identified the extent to which the community accept their ideas and contributions to the nation and country. The methods used to produce this writing were survey on archival materials, library sources, interviews, and internet sources. The research findings summarized that their thoughts were transformed into struggles, which led to independence and progress of the nation. Struggles of Gandhi were more prominent before the independence of India, but the struggles of Sambanthan reached its peak after the independence of Malaya. Gandhi struggled for all the people irrespective of race, religion and caste but Sambanthan’s struggles were more specific to the Indian community of Malaya. Through this research, it was also identified that most of the writings on Sambanthan only stated briefly that he was a loyal follower of Gandhi but there are no further explanations on it. Hence, this thesis details the relationship between them and proved their thoughts, struggles and contributions can be compared in a meaningful way.